Mindful organizing in patients’ contributions to primary care medication safety - Phipps, Denham L.; Giles, Sally; Lewis, Penny J.; Marsden, Kate; Salema, Ndeshi; Jeffries, Mark; Avery, Anthony J.; Ashcroft, Darren M. (Wiley, 2018)
Background: There is a need to ensure that the risks associated with medication usage in primary healthcare are controlled. To maintain an understanding of the risks, healthcare organizations may engage in a process known as “mindful organizing”. While this is typically conceived of as involving organizational members, it may in the healthcare context also include patients. Our study aimed to examine ways in which patients might contribute to mindful organizing with respect to primary care medication safety.